Surgical complications in the post-operative period in 1.478 gastrectomies due to ulcus. - Matteucci, Pablo; Geninazzi, Héctor; Lerena, Ana; Ricciardi, Norma; Cefrorella, Nora (Cirugía del Uruguay, 1984)
Study on surgical complications in 1.478 gastrectomies in cases of ulcus, performed at the Clinical Hospital • Montevideo, over a period of 26 years, remarking severe cases and the high mortality rate.